(untitled) (Bangladesh Journal of Medicine, 2022)
Background: Malnourishment is highly prevalent among COPD patients. The study was carried out to assess the nutritional status of hospital admitted COPD patients to evaluate the relationships between the nutritional indices and the pulmonary function parameters with severity correlation. Methods: A cross-sectional observational study was done constituting 50 spirometryproven COPD patients admitted at Dhaka Medical College Hospital. Lung function was measured by routine spirometry. Anthropometric measures, biochemical parameters, and Mini Nutritional Assessment (MNA) score were used for nutritional assessment. Results: Mean age of study population was 64.31 years.22% (n = 11), 42% (n = 21) 32% (n = 16) & 4% (n = 2) of the patients were of stage I, II, III and IV of COPD respectively.According to MNA scalethe study population were malnourished 46% (n = 23), at risk of malnutrition 40% (n = 20) and normal nutritional status 14% (n = 7).13 patients were found malnourished according to BMI scale and were in stage I COPD 15.38% (n = 2), stage II 38.46% (n = 5), stage III 38.46% (n = 5) and stage IV 7.69% (n = 1). Mid arm circumference (MAC), mid-calf circumference (MCC), MNA scale score and BMI score showed a significant decline of mean value with increasing severity of stages of COPD. The correlation between BMI and FEV1 (R2 = 0.087 and p value= 0.038), body weight and FEV1 (R2 = 0.173 and p value= 0.003), MUAC and FEV1 (R2: 0.202, p value = 0.001) and MNA scale and FEV1 (R2 = 0.144 and p value= 0.007). All correlations were statistically significant. Conclusion: The high prevalence of malnutrition among hospitalized COPD patients is related to their lung function. Weight, mean MNA, and BMI score decrease with increasing severity of COPD. Bangladesh J Medicine 2022; 33: 186-192